2012
DOI: 10.1210/en.2011-1423
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Cannabinoid Receptor 1 Improves Insulin Resistance, Lipid Metabolism, and Diabetic Nephropathy in db/db Mice

Abstract: The endocannabinoid system is important in the pathogenesis of obesity-related metabolic disorders. However, the effect of inhibiting the endocannabinoid system in type 2 diabetic nephropathy is unclear. Therefore, we examined the effect of the cannabinoid (CB)1 receptor antagonist, SR141716, on insulin resistance and diabetic nephropathy in db/db mice. Six-week-old db/db mice were treated with the CB1-specific antagonist SR141716 (10 mg/kg · d) for 3 months. Treatment with SR141716 significantly improved insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(123 citation statements)
references
References 41 publications
9
113
0
1
Order By: Relevance
“…Indeed, it is possible that the improvements in insulin sensitivity that are conveyed by rimonabant in aged mice may be due, at least in part, to reductions in adiposity. However, it should be noted that previous studies utilizing hyperinsulinaemic‐euglycaemic clamps and/or ITT (insulin tolerance test), have documented the ability of rimonabant to improve insulin sensitivity without promoting significant reductions in body fat mass or visceral fat in db/db mice and diet‐induced obese dogs, respectively (Kim et al ., 2012; Nam et al ., 2012). Together with our previous work reporting direct insulin‐sensitizing actions by rimonabant in rat skeletal L6 myotubes (Lipina et al ., 2010), these findings indicate that CB1R inhibition may at least partly enhance insulin sensitivity in aged mice independently of its ability to normalize age‐related adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is possible that the improvements in insulin sensitivity that are conveyed by rimonabant in aged mice may be due, at least in part, to reductions in adiposity. However, it should be noted that previous studies utilizing hyperinsulinaemic‐euglycaemic clamps and/or ITT (insulin tolerance test), have documented the ability of rimonabant to improve insulin sensitivity without promoting significant reductions in body fat mass or visceral fat in db/db mice and diet‐induced obese dogs, respectively (Kim et al ., 2012; Nam et al ., 2012). Together with our previous work reporting direct insulin‐sensitizing actions by rimonabant in rat skeletal L6 myotubes (Lipina et al ., 2010), these findings indicate that CB1R inhibition may at least partly enhance insulin sensitivity in aged mice independently of its ability to normalize age‐related adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that XLR-11 and UR-144 had Δ9-THS-like activity in animals and bind to the brain cannabinoid receptor (CB1 receptor) in in vitro studies. CB1 receptors are also expressed in kidney cells, including podocytes and proximal tubule cells (10)(11)(12), and we suggest that the AKI related to SCB might be related to CB1 receptors in the kidneys. Th ere are limited data on the CB1 receptor and kidney function.…”
Section: Synthetic Cannabinoids and Acute Kidney Injurymentioning
confidence: 72%
“…Th ere are limited data on the CB1 receptor and kidney function. However, blockade of CB1 receptors has been shown to have protective eff ects on renal function and ameliorate albuminuria in certain groups of mice (10,11,13).…”
Section: Synthetic Cannabinoids and Acute Kidney Injurymentioning
confidence: 99%
“…Several recent reports (Table 1) have documented the presence of functional CB 1 receptor in the entire kidney [15,[33][34][35][36][37][38][40][41][42], including different parts of the nephron such as afferent and efferent arterioles [39], glomeruli [33,38,40,42,43], tubules [15], the loop of Henle [44], and collecting ducts [15]. It is also expressed in various subtypes of kidney cells such as podocytes [33,41,43,45,46], proximal and distal tubular epithelial cells [15,34,37,38,40,41,[47][48][49], and mesangial cells [50,54]. Moreover, CB 1 receptors are expressed in human clear-and chromophobe-renal cell carcinomas, as well as in renal oncocytoma [55,56].…”
Section: The Renal Ecb Systemmentioning
confidence: 99%
“…To date, two murine models for type 2 DM have been utilized to test the involvement of CB 1 receptor in DN. Using the diabetic db/db mouse model, Nam et al [43] documented preferentially increased CB 1 receptor expression in glomerular podocytes and demonstrated that SR141716 treatment significantly inhibits the expression of profibrotic and proinflammatory molecules in the diabetic kidney. Insights into the mechanism by which the CB 1 receptor modulates podocyte injury in type 2 DM were found in a recent report by Jourdan et al [41], who used the well-established Zucker diabetic fatty (ZDF) rat model.…”
Section: Role Of Cb 1 Receptors In Dnmentioning
confidence: 99%